Adjustment policies in developing countries, 1979-83 : an update - Balassa, Bela (World Bank Washington DCUS, 1984)
Discusses impact of four external shocks viz. the increase in oil prices in 1979-80, the slow down of world economy after 1978, the rise in interest rates starting in late 1978, and the softeneing of commodity prices in 1981 and 1982, on 30 developing countries and examines effect of policies applied in dealing with those shocks. Updates analysis of policies applied by developing countries in response to external shocks of the 1979-82 period, extending investigation to 1983.